Analysis of success in soccer according to the maximum level of achievement: the goal - Mario Sánchez García; Begoña Orgaz Baz; Óscar Chamorro Martínez; Manuel Carretero González; Javier Sánchez Sánchez (E-balonmano.com: Revista de Ciencias del Deporte, 2019)
The aim of this study was to describe and analyze the percentage of goals achieved with respect to the number of shots on goal and the probability of success, related to the demarcation of the player, the body region with which the action is executed and the spatial context from which makes. 733 shooting actions (goal = 99) of the UEFA Champions League qualifying round 16-17 were analyzed and recorded by means of an instrument developed ad hoc. The forwards obtained a high level of success, unlike the lateral defenses, which obtained a low level. The probability of success of getting a goal with the head was similar to the one of the right foot, being the central defender the demarcation that more goals obtained with this corporal region. The level of success from the central corridor (PC) was high, while from the side corridors (PLD and PLI) it was very low. In the sector-corridor relationship, from PC, the level of success was high in the offensive sector (SO) and very low in the offensive middle sector (SMO). Within zone 11, in subzone 11.5 it was from where more shots were made but with a low probability of success. In sub-area 11.1 the number of shots was low but they obtained a high probability of success. Subzone 11.2 obtained a low probability of success with the head and upper body region with the right body region. It is important that the coaches know that demarcations, corporal regions of execution of the action and zones of the field have a greater probability of success to be able to plan their training and improve the performance of their players.